Konsekuensi Akibat Perubahan Status Organisasi Papua Merdeka Sebagai Teroris Dalam Hukum Pidana - Alfarizky, Hamdallah; Risyanto, Asyraf Putra (Media Hukum Indonesia (MHI), 2024)
Many workers in Indonesia experience violations of legal protection of their Based on history, acts of violence carried out by certain groups in Papua have various names. The police call them the Armed Criminal Group (KKB), while the Indonesian National Army (TNI) uses the term Armed Separatist Group (KSB). The Free Papua Organization (OPM) considers this group to be fighters trying to separate themselves from Indonesia. A series of attacks by the KKB/KSB/OPM on security forces in Papua prompted the government to designate these acts of violence as criminal acts of terrorism. This research seeks to examine the feasibility of this status and its consequences. Through normative research methods, it was concluded that designating the OPM/Armed Criminal Group (KKB) as a terrorist group was considered appropriate because the assessment was based on the acts of violence committed, not on the history or initial goals of the formation of the OPM. Determination of this status has an impact in three main aspects: formal legal provisions, material legal provisions, as well as the law enforcement institutions involved, including prevention and treatment patterns. This research uses normative methods with statutory, conceptual and case study approaches. Granting terrorist status This is considered ineffective for resolving the conflict in Papua because it can affect the classification of criminal acts that occur, the legal instruments used, as well as law enforcement methods and the parties involved in handling them.